Hahnemann and nutrition - Hehr, G.S. (British Homeopathic Journal, 1981)
Our knowledge of the chemical structure and physiological role of various food factors is only recent. It has been possible to correlate appetite for some particular foods with body needs. We have an in-built mechanism in our body that guides us in the matter of quality and quantity of food we need. This has been proved by many recent scientific experiments. Hahnemann had recognised this fact about two centuries back and had devised methods of ensuring adequate nutrition in health and in disease. Recent evidence confirms the effectiveness of these methods.